Macroeconomic Influence on the Nepalese Stock Market - Khatri, Mukti Bahadur (NRB Economic Review, 2019)
This study examines the dynamic relationship among the stock market and macroeconomic factors such as nominal domestic variables (inflation, money supply, and interest rate), real economic activity (gross domestic product) and foreign variable (exchange rate and foreign direct investment) of Nepal. It has used Johansen and Juselius (1990) method of multivariate cointegration for the period Mid-July 1994 to Mid-July 2015. The finding of this study shows that the stock prices are positively and significantly related to money supply. Real economic activity and interest rate have insignificant and negative relationship with the stock prices. Similarly, foreign direct investment, inflation (CPI) and exchange rate with US dollar have a positive and insignificant relationship with the Nepalese stock market. Accordingly, the VEC estimates suggest that there is no significant effect of macroeconomic variables to the Nepalese stock price in the short run. In general, the presence of cointegration and causality suggest that Nepalese stock market is not efficient in both the short run and the long run.